Progress and challenges associated with the development of ricin toxin subunit vaccines. (1st September 2016) - Vance, David J.; Mantis, Nicholas J.
ABSTRACT: The past several years have seen major advances in the development of a safe and efficacious ricin toxin vaccine, including the completion of two Phase I clinical trials with two different recombinant A subunit (RTA)-based vaccines: RiVax™ and RVEc™ adsorbed to aluminum salt adjuvant, as well as a non-human primate study demonstrating that parenteral immunization with RiVax elicits a serum antibody response that was sufficient to protect against a lethal dose aerosolized ricin exposure. One of the major obstacles moving forward is assessing vaccine efficacy in humans, when neither ricin-specific serum IgG endpoint titers nor toxin-neutralizing antibody levels are accepted as definitive predictors of protective immunity. In this review we summarize ongoing efforts to leverage recent advances in our understanding of RTA-antibody interactions at the structural level to develop novel assays to predict vaccine efficacy in humans.